1997
DOI: 10.1177/026921559701100207
|View full text |Cite
|
Sign up to set email alerts
|

Subjective well-being one year after stroke

Abstract: Subjective well-being is decreased one year after stroke, and this is mainly attributed to arm motor impairments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(73 citation statements)
references
References 21 publications
0
71
0
1
Order By: Relevance
“…Problems of praxis foUowing stroke have been found to affect the weUbeing ofthe patient up to one year later (WyUer et al, 1997), However, these problems have not been found to impact on sttain in spouses of stroke patients, ft is often difficuh to distinguish between dyspraxia and disorders of language and communication and many tests require a degree of language and expression in order to complete. Nevertheless, one reason for selecting Kertesz and Ferro' …”
Section: 35mentioning
confidence: 99%
“…Problems of praxis foUowing stroke have been found to affect the weUbeing ofthe patient up to one year later (WyUer et al, 1997), However, these problems have not been found to impact on sttain in spouses of stroke patients, ft is often difficuh to distinguish between dyspraxia and disorders of language and communication and many tests require a degree of language and expression in order to complete. Nevertheless, one reason for selecting Kertesz and Ferro' …”
Section: 35mentioning
confidence: 99%
“…É uma complicação muito freqüente e suas causas e tratamento adequado ainda não estão claramente estabelecidos 26 . Além disso, resulta em grande impacto negativo sobre a recuperação funcional de pacientes que sobrevivem a um AVE [4][5][6][7] . Devido à importância e à necessidade de medidas profiláticas precoces, apontadas por vários autores 1,15,16 , o tratamento fisioterapêutico proposto para esse estudo foi iniciado nas primeiras 48 horas pois, em cerca de 20% dos pacientes, a dor no ombro H/ P pode surgir já na 1 a e 2 a semana pós ictal [8][9][10] .…”
Section: Métodounclassified
“…Approximately 85 percent of patients with stroke do not regain upper-limb function and remain dependent on caregivers [2][3], with motor impairments accounting for most poststroke disability [4]. Loss of upper-limb function is a major cause of poor perception of well-being following stroke [5].…”
Section: Introductionmentioning
confidence: 99%